The Effect of Temperature, pH, and Different Solubilizing Agents on Stability of Taxol: Stability of taxol in solutions - Montaseri, Hashem; Jamali, Fakhrodin; Rogersb, Jim A.; Micetich, Ronald G.; Daneshtala, Mohsen (Iranian Journal of Pharmaceutical Sciences, 2005)
Inabilities to attain adequate aqueous solubility and stability have made the preparation of a clinically suitable formulation of taxol difficult. Addition of nicotinamide (ND), 2-hydroxypropyl-b-cyclodextrin (HPßCD), polyethylene glycol, (PEG), bile salts (BS, 50:50 sodium cholate: deoxycholate), and cremophor EL can improve the solubility of taxol. Studies were undertaken to compare the stability of taxol in HPßCD (20%), ND (20%), PEG (20%), BS (20%), and cremophor EL (cremophor: ethanol 0.5% of each) solutions at 25, 37, 50, and 60 oC. Taxol concentration was measured by HPLC method. The rate of degradation proceeded in a Log-linear fashion and increased progressively with the elevation of temperature in all solutions except in HPbCD which taxol had negligible degradation. In the absence of added agents, taxol exhibited the lowest and highest stability at pH 1.2 and 4.5, respectively. Taxol was most stable in HPbCD followed by PEG and then ND. The stability of taxol increased linearly with the HPbCD concentration (0-5% w/v). Due to the observed improved stability and solubility, HPbCD may be considered for pharmaceutical studies as a suitable stabilizer for formulation of taxol.